Efficacy and safety of remifentanil dose titration to correct the spontaneous hyperventilation in aneurysmal subarachnoid haemorrhage: protocol and statistical analysis for a prospective physiological study - Xiaolin Chen; Jian-Xin Zhou; Rui Su; Jianfang Zhou; Ning Zhu; Hong-Liang Li (BMJ Open, 2022)
Introduction Spontaneous hyperventilation (SHV) is common in aneurysmal subarachnoid haemorrhage (aSAH). The reduction in arterial partial pressure of carbon dioxide (PaCO2) may change the brain physiology, such as haemodynamics, oxygenation, metabolism and may lead to secondary brain injury. However, how to correct SHV safely and effectively in patients with aSAH has not been well investigated. The aim of this study is to investigate the efficacy and safety of remifentanil dose titration to correct hyperventilation in aSAH, as well as the effect of changes in PaCO2 on cerebral blood flow (CBF).Methods and analysis This study is a prospective, single-centre, physiological study in patients with aSAH. The patients who were mechanically ventilated and who meet with SHV (tachypnoea combined with PaCO2 <35 mm Hg and pH >7.45) will be enrolled. The remifentanil will be titrated to correct the SHV. The predetermined initial dose of remifentanil is 0.02 μg/kg/min and will be maintained for 30 min, and PaCO2 and CBF will be measured. After that, the dose of remifentanil will be sequentially increased to 0.04, 0.06, and 0.08 μg/kg/min, and the measurements for PaCO2 and CBF will be repeated 30 min after each dose adjustment and will be compared with their baseline values.Ethics and dissemination This study has been approved by the Institutional Review Board of Beijing Tiantan Hospital, Capital Medical University (KY 2021-006-02) and has been registered at ClinicalTrials.gov. The results of this study will be disseminated through peer-reviewed publications and conference presentations.Trial registration number NCT04940273.